A qualitative evaluation of a co‐design process involving young people at risk of suicide - Michelle Kehoe; Rick Whitehead; Kathleen deBoer; Denny Meyer; Liza Hopkins; Maja Nedeljkovic (Health Expectations)
Abstract Background Co‐design is becoming common practice in the development of mental health services, however, little is known about the experience of such practices, particularly when young people are involved. Objective The aim of this study was to conduct a process evaluation of the co‐design which was undertaken for the development of an intervention for youth and adolescents at risk of suicide. This paper briefly outlines the co‐design process undertaken during a COVID‐19 lockdown and then focuses on a qualitative evaluation of the experience of taking part in a co‐design process. Setting and Participants The evaluation involved young consumers of a public youth mental health service, their carers/parents and service delivery staff who had taken part in the co‐design process. Method This study used follow‐up semistructured interviews with the co‐design participants to explore their experience of the co‐design process. Inductive thematic analysis was used to draw out common themes from the qualitative data. Results It was found that despite the practical efforts of the project team to minimise known issues in co‐design, challenges centred around perceptions regarding power imbalance, the need for extensive consultation and time constraints still arose. Discussion Despite these challenges, the study found that the co‐design provided a human‐centred, accessible and rewarding process for young people, parents and staff members, leaving them with the feeling that they had made a worthwhile contribution to the design of the new service, as well as contributing to changing practice in service design. Conclusion With sensitivity and adaptation to usual practice, it is possible to include young people with suicidal ideation, their parents/carers and professional staff in a safe and effective co‐design process. Patient and Public Contribution The authors would like to thank and acknowledge the young people with a lived experience and their carers who participated in the co‐design process and research evaluation component of this study. We also wish to thank the clinical staff, peer workers and family peer workers who participated in this research.